2013
DOI: 10.1016/j.crme.2013.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the Soret coefficients in organic/water mixtures by thermal lens spectrometry

Abstract: In this work we utilize an alternative optical method based on thermal lens spectroscopy for characterizing the thermal diffusion in binary liquid mixtures. In this method, the thermal lens and the Soret signals are separated by a time interval to determine the Soret coefficients. As a demonstrative experiment, the Soret coefficients of isopropanol/water and acetone/water mixtures have been measured using that variant. Our results were compared with the recently published experimental and theoretical calculati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“… 3 , 4 Recognition of the advantages of sensitivity and label-free nature have led to rapid development of linear photothermal methods in the visible region, both for spectroscopy and microscopy. 5 8 Photothermal spectroscopy has been used to characterize weak absorption 9 11 in solids and liquids and for spectroscopy of heme proteins and imaging in mitochondria. 5 , 6 Zharov 12 15 and co-workers have extended photothermal and photoacoustic spectroscopy to the nonlinear regime with reported splitting and sharpening of photothermal spectral signatures in the visible.…”
mentioning
confidence: 99%
“… 3 , 4 Recognition of the advantages of sensitivity and label-free nature have led to rapid development of linear photothermal methods in the visible region, both for spectroscopy and microscopy. 5 8 Photothermal spectroscopy has been used to characterize weak absorption 9 11 in solids and liquids and for spectroscopy of heme proteins and imaging in mitochondria. 5 , 6 Zharov 12 15 and co-workers have extended photothermal and photoacoustic spectroscopy to the nonlinear regime with reported splitting and sharpening of photothermal spectral signatures in the visible.…”
mentioning
confidence: 99%
“…Due to the fluorescence quenching mentioned above, the non-radiative recombination mechanisms following light absorption become important. This fact makes the use of photothermal [20] characterization tools useful, in particular thermal lens based methods [18,19]. Malacarne et al [21] reported a theoretical model and experimental results for laser-induced local heating in liquids, and proposed a method to detect and quantify the contributions of photochemical and Soret effects in several different situations.…”
Section: Introductionmentioning
confidence: 99%
“…The applied TLM technique is based on the counter propagating pump-probe beams [17] in the mode-mismatched optimized [18,19] thermal lens (TL) configuration. Due to the fluorescence quenching mentioned above, the non-radiative recombination mechanisms following light absorption become important.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Eqs. (6), (8) and (9) hold in general, for an arbitrary number of components, which opens the way to a possible description of thermodiffusion in a frame-independent way.…”
Section: Extension To Multi-component Mixturesmentioning
confidence: 99%